The Effect Of Peppermint Aromatherapy On The Frequency Of Nausea And Vomiting In Pregnant Women In The First Trimester At Pmb Nurhidayah - Sri Wulandari; Sandiva Voleta; Rika Herawati; Andria (CV. AFDIFAL MAJU BERKAH, 2025)
Nausea and vomiting are normal symptoms that commonly occur in pregnant women in the first trimester. For pregnant women in the first trimester, nausea and vomiting occur in the 9th to 10th week of pregnancy, with peak symptoms between the 11th and 13th weeks. The impact of nausea and vomiting in some pregnant women with severe symptoms will result in hyperemesis gravidarum. The incidence of hyperemesis gravidarum cases is 0.8% to 3.2% of all pregnancies or around 8 to 32 cases per 1000 pregnancies. The incidence of Hyperemesis Based on data from Rokan Hulu Hospital medical records, there were 480 pregnant women from January 2015 to April 2016, namely 196 pregnant women experienced Hyperemesis Gravidarum. Research purpose : to determine the effect of Peppermint Aromatherapy on the Frequency of Nausea and Vomiting in Pregnant Women in the First Trimester at PMB Nurhidayah. Method: This type of research is quantitative with a pre-experimental research design with a pretest and posttest design approach using the NRS observation sheet. The sample in this study was 10 people. The sampling technique was a saturated sample. Data analysis used univariate and bivariate. Results: the results of the study, it is known that the univariate average obtained by the pretest average is 5.60 with a standard deviation of 0.966. While the posttest average is 3.00 with a standard deviation of 0.816. The results of the T-Test test obtained a p value of 0.000 (p <0.05). This shows that there is a significant difference in the average frequency of nausea and vomiting before and after giving Peppermint Aromatherapy Against the Frequency of Nausea and Vomiting in Pregnant Women in the First Trimester at PMB Nurhidayah. Conclusion: With this study, it is hoped that it can add references or insight into peppermint aromatherapy to relieve nausea and vomiting in pregnant women.